Association of perioperative step count tracked by a wristband with surgical outcomes in minimally invasive lung cancer surgery: a prospective observational study - Yuanyuan Yao; Ying Wang; Yi Liu; Yang Yu; Xuena Wang; Xuena Wang; Tingting Wang; Bin Zheng; Min Yan (Frontiers in Medicine)
BackgroundPhysical activity has been reported to be associated with surgical outcomes, but most previous studies have focused solely on postoperative step counts. To better understand the relationship between step count at different phases and surgical outcomes, we prospectively recorded patients’ step counts before and after lung surgery.MethodsStep count data were collected from 244 patients who underwent minimally invasive surgery for lung cancer using Mi Band 5 to track preoperative and 3-day postoperative activity. Patients’ quality of life was assessed using the 12-Item Short Form Health Survey (SF-12) preoperatively and at 1 and 3 months postoperatively. Correlation and regression analyses were conducted to evaluate the impact of perioperative step count on hospital length of stay and quality of life.ResultsPreoperative (r = −0.146, p = 0.023) and postoperative day 1 (r = −0.172, p = 0.018) step count were significantly correlated with the length of hospital stay. Postoperative day 1 step count was positively correlated with changes in SF-12 Physical Component Score (PCS) at 1 month (r = 0.186, p = 0.013). Pain significantly affected PCS changes at both 1 (β = −3.33, p < 0.001) and 3 months (β = −3.06, p < 0.001).ConclusionHigher preoperative step counts are associated with a shorter hospital stay, while early postoperative physical activity is linked to both reduced hospital stay and improved short-term quality of life.Clinical trial registrationClinicaltrials.gov, identifier NCT 04934657.